REALIZATION OF VISUAL TECHNIQUE DIDACTIC APPROACH IN ALGORITHMIC TRAINING OF STUDENTS THROUGH INFORMATION AND COMMUNICATION TECHNOLOGIES OF EDUCATIONAL ENVIRONMENT - Sergii Voloshynov; Oksana Kostyuchenko; Natalia Osipova (Kherson State University, 2016)
The article examines the development of visual learning theory, states functions of accuracy and peculiarities of visual technique realization in modern studying process, it defines the concept of "Visual learning environment" and didactic role of interactive and multimedia visualization processes. Author examines the problem of determination of cognitive visualization potential in algorithmic training of students through information and communication technologies of educational environment. This article specifies functions of visual aids use and implementation features of the specified principle in modern educational process and proves the didactic role of interactive multimedia visualization process that stimulates cognitive activity of student and activates perceptive mechanism of teaching information. It analyzes problem of cognitive visualization potential capacity signification while training future marine personnel using informational communicative educational environment.